46‐2: Invited Paper: Strip‐Helix‐Fiber Architecture for Stretchable TFTs and Circuits - Nathan, Arokia; Yu, Jun; Jiang, Chen; Ma, Hanbin (SID International Symposium Digest of technical papers, 2022)
This paper reviews design considerations for ultralow power thin‐film transistor and amplifier circuits with high stretchability for newly emerging wearable applications. To achieve high stretchability, the device/circuit is layered on an active strip fiber that is coiled in a helical pattern around a core carrier‐fiber. This results in a helical strain of the device/circuit to below 1% despite the core carrier‐fiber being subject to an external strain of 50%. The active helical strip fiber architecture comprises a low‐voltage organic thin‐film transistor and amplifier operating in deep‐subthreshold regime. The thin film transistor and amplifier is layered entirely using inkjet printing technology. The highly stretchable amplifier has a high voltage gain of 214 V/V with subthreshold transconductance efficiency of 0. 6q/kT and ultralow power consumption of 681 pW.